Strong thermomechanical noise squeezing stabilized by feedback - Aida Mashaal; Lucio Stefan; Andrea Ranfagni; Letizia Catalini; Ilia Chernobrovkin; Thibault Capelle; Eric C. Langman; Albert Schliesser (Physical Review Research)
Squeezing the quadrature noise of a harmonic oscillator enhances its sensitivity. Stabilization of the antisqueezed quadrature can overcome the 3 dB squeezing limit by parametric modulation. Here, we apply this method to soft-clamped membrane resonators, which hold promise for both classical and quantum sensing applications. We compare piezoelectric and capacitive parametric modulation and observe thermomechanical squeezing by up to 17 and 21 dB, respectively. Finally, we provide a full quantum theory of combining this approach with quantum-limited motion measurement. We conclude that quantum squeezing is feasible at moderate cryogenic temperatures and realistic device parameters.